Dwi Kewarganegaraan Bupati Terpilih di Sabu Raijua (Analisis Putusan Mahkamah Konstitusi Nomor: 133/134/135/PHP.BUP-XIX/2021) - Nadia Desfarika; Azzubaili; Nur Sari Dewi. M (TANFIDZIY, 2023)
The Citizenship Status of the elected Regent in Sabu Raijua attracts the attention of various parties about Orient who is known to have an American Passport, but he is also registered as an Indonesian Citizen and has original Population Documents such as e-KTP, while if an Indonesian citizen has dual citizenship, his status as an Indonesian citizen will be canceled. This article is reviewed using the Normative Juridical research method. Based on the results of the study, it explains that the dual citizenship provisions for nominating regional officials that apply in Indonesia are that they must be Indonesian citizens other than that in Law Number 12 of 2006 concerning Citizenship which provides a time limit for having dual citizenship with an age limit of 18 years. The reason the elected regent Orient Riwu Kore was canceled by the Constitutional Court Decision was because it was known that Orient's brother had an active United States Passport and this was contrary to Law Number 12 of 2006 concerning Citizenship.